2013
DOI: 10.1155/2013/712758
|View full text |Cite
|
Sign up to set email alerts
|

What We Have Learned about Autism Spectrum Disorder from Valproic Acid

Abstract: Two recent epidemiological investigations in children exposed to valproic acid (VPA) treatment in utero have reported a significant risk associated with neurodevelopmental disorders and autism spectrum disorder (ASD) in particular. Parallel to this work, there is a growing body of animal research literature using VPA as an animal model of ASD. In this focused review we first summarize the epidemiological evidence linking VPA to ASD and then comment on two important neurobiological findings linking VPA to ASD c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 97 publications
1
65
0
Order By: Relevance
“…VPA is primarily used as a drug for seizure and epilepsy control in humans. VPA has long been known to cause developmental disabilities and physical malformations (Chomiak et al, 2013). Recently, a large-scale population-based study demonstrated that prenatal VPA exposure significantly increases the risk of ASD (Bromley et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…VPA is primarily used as a drug for seizure and epilepsy control in humans. VPA has long been known to cause developmental disabilities and physical malformations (Chomiak et al, 2013). Recently, a large-scale population-based study demonstrated that prenatal VPA exposure significantly increases the risk of ASD (Bromley et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high doses of the monocarboxylic HDAC inhibitors propionate or valproate, administered either systemically to the mother during pregnancy or intraventricular in adulthood were repeatedly shown to induce autistic-like symptoms in animal models (Chomiak et al, 2013;Macfabe, 2012;MacFabe et al, 2011MacFabe et al, , 2007Roullet et al, 2013;Thomas et al, 2012), suggesting extreme care has to be given to evaluation of the potential use of SCFAs in treatment of ASDs. Interestingly, however, the prenatal valproate-induced mouse model could also be treated with butyrate or even valproate when given at 4 weeks of age for 5 weeks, which was accompanied by increased histone H3 acetylation in the case of butyrate (Takuma et al, 2014).…”
Section: Histone Acetylation In Psychiatric Disordersmentioning
confidence: 99%
“…Owing to this correlation between in-utero VPA exposure and the increased risk of autism, the VPA rodent model was developed (Rodier et al, 1996;Arndt et al, 2005;Bromley et al, 2009Bromley et al, , 2013Bath and Scharfman, 2013). Pregnant dams exposed to a single dose of VPA on gestational day 12.5 produce progeny that show behavioral and neuroanatomical anomalies that are similar to those present in humans with autism (Rodier et al, 1996(Rodier et al, , 1997Schneider and Przewlocki, 2005;Rinaldi et al, 2008;Snow et al, 2008;Mychasiuk et al, 2012;Chomiak et al, 2013).…”
Section: Introductionmentioning
confidence: 99%